Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, dan Kecerdasan Spiritual terhadap Kinerja Karyawan dengan Profesionalisme sebagai Variabel Intervening - Bunga Aditi; Aulia Nurul Hidayah; Maisara batubara (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2021)
One of the roles of human resource management is to maintain and improve employee performance. The purpose of this study is to find out whether intellectual intelligence, emotional intelligence, and spiritual intelligence affect employee performance through professionalism as an intervening variable. The population in this study was PDAM Tirtanadi North Sumatra employees who had worked for more than 5 years, with a total research sample of 105 employees. This type of research is associative research with a quantitative approach. The results showed that intellectual intelligence, emotional intelligence, and spiritual intelligence had a positive and significant effect on the performance of PDAM Tirtanadi employees in North Sumatra Province. There is a positive and significant influence of intellectual intelligence on professionalism, while emotional intelligence, and spiritual intelligence on the performance of PDAM Tirtanadi North Sumatra Province, there is an influence of professionalism on employee performance of PDAM Tirtanadi North Sumatra Province, there is an influence of intellectual intelligence, emotional intelligence and spiritual intelligence on employee performance through professionalism.